Fish Diversity in The Seagrass Beds of Labuhan Sangoro Waters, Sumbawa - Gusfina, Omira Calia; Karnan, Karnan; Syukur, Abdul (Jurnal Biologi Tropis, 2025)
The waters of Labuhan Sangoro in Sumbawa have seagrass beds that function as important habitats for various fish species. Information on fish diversity in this area plays an important role in supporting conservation efforts and management of aquatic resources. This study aims to analyze the level of fish diversity in the Labuhan Sangoro seagrass bed area, Sumbawa Regency, West Nusa Tenggara Province. Sampling was carried out in three locations selected based on differences in habitat characteristics, namely mangrove areas, areas with natural ecological conditions, and areas adjacent to residential areas. The data collection method used a gill net with a length of 25 meters and a width of 1 meter, and two mesh sizes, namely 1.5 inches and 2 inches. The nets were installed at each predetermined location to represent the variation of existing habitats. This approach aims to ensure that the data obtained can reflect the real conditions regarding the distribution and abundance of fish species in the seagrass bed area. The results of the study showed that the diversity of seagrass fish in the waters of Labuhan Sangoro, Sumbawa, was at a moderate level (H’ = 2.91), with a low level of species dominance (D = 0.06), indicating that no species dominated significantly. The high level of evenness (E = 0.92) reflects a relatively even distribution of individuals between species. Overall, the aquatic ecosystem in this area shows a relatively balanced condition and supports moderate biodiversity, with an even distribution of species and no dominance of certain species.